Использование метода кейс-стади как образовательной технологии - Амантаева, А.Б. (My University, 2016)
This technology is aimed at independent or group work of students on the study of information and documents describing the state and development of a particular practical situation, the purpose of which is 32 the activation of cognitive activity of students in the classroom.Technology "Case Study" allows you to apply the theoretical knowledge to solve practical problems, is the most successful and common learning practical skills with minimal teacher
Keywords: method; innovative technology; "case studies"; the learning process; the student; the activation; cognitive activity